Improved visualisation of a coronary artery fistula by the "laid-back" aortogram. Issue 3 (September 1993) - Hofbeck, M; Wild, F; Singer, H
Abstract : The preoperative assessment of patients with a coronary artery fistula requires exact angiographic evaluation of the coronary artery anatomy. A technique of transvenous balloon occlusion angiography of the aorta is described. This can be applied easily in infants with a persisting foramen ovale. Combination of this technique with the so-called "laid-back" aortogram gave excellent visualisation of a fistula between the right coronary artery and the right ventricle. This technique is a major improvement in the angiographic assessment of infants with coronary artery abnormalities and normal cardiac connections.